Learning from Japan's Experience in Integrated Urban Flood Risk Management : A Series of Knowledge Notes - World Bank (World Bank, Washington, DC, 2020)
Globally, floods are the most frequent and damaging natural hazard. This poses a serious development challenge to many countries and their efforts to reduce poverty and increase shared prosperity. To help manage the impact of floods on people and economies, the World Bank provides technical assistance, advisory services, and financial support to a range of countries and cities around the world. Facing different types and combinations of flood risk, Japan’s rich history, range of investments and approaches taken offers a unique knowledge opportunity for other countries seeking to adopt and advance integrated urban flood risk management (IUFRM). This series of knowledge notes compiles many of the key lessons learned from Japan’s IUFRM efforts. While any strategy to reduce disaster risk must be developed based on a close understanding of local contexts, the aim of this series is to help members of the international community improve their own approaches to managing urban floods. These notes are not intended to provide a comprehensive analysis but rather a snapshot highlighting key aspects, practice and lessons learnt from Japanese practice. The four knowledge notes in this series cover urban floods from assessment and planning through to implementation and maintenance.